New Directions for Disadvantaged Adults in the Community College - Giroux, Roy F.; Pietrofesa, John J. (Canadian Journal of Counselling and Psychotherapy, 2012)
There is a need today for new methods of helping disadvantaged adults and youth through community colleges. Canadian community colleges can help in the delivery of educational and service programs to a long neglected student. This article describes a life-skills program with its major objective to assist disadvantaged adults in obtaining employment opportunities. There is a need for faculty to respond to the culturally different, for a new curriculum which has been modified to their needs, and for new teaching consistent with learning styles of the alienated. Specific program guide-lines are presented.